The brainworkers : typology, training background and work situation. A report from the FAST-Programme of the Commission of the European Communities - Gizycki, Rainald von [Verfasser]; Ulrici, Wolfgang [Verfasser] (Oldenbourg, 1988)
"The brainworker is a new type of intellectual worker arising in technology minded industrial settings. He struggles with those new requirements in research and development (but also in systems application) which stem from the drastic reduction of innovation cycles and from the increasing integration of technologies into ever broader "Systems". He is neither a hardware man nor a software man, neither a mechanical nor an electronic engineer, neither a business manager nor a technical entrepreneur - he is all of this en miniature." The report presents the results of a study carried but by the Battelle Institut e.V., Frankfurt a.M., for the FAST programme of the Commission of the European Communities. The aims of the study are: "- to define the concept of the "brainworker", - to review the available estimates of the quantitative evolution of "brainworkers", - to find matching empirical positions/activities in selected organizational settings, - to characterize the type of socio-demographic background and the career of "brainworkers", - to characterize the working situation of "brainworkers" in selected "habitats", - to analyze the training and retraining background of "brainworkers", - to make suggestions concerning possible Community action aiming at improving the conditions for the emergence and growth of "brainworkers"." (IAB2) Der Bericht enthält die Ergebnisse einer Studie, die im Rahmen des FAST-Programms der EG durchgeführt wurde und folgende Ziele anstrebte: - Definition des Konzepts "brainworker", - Bericht über die vorhandenen Schätzungen zur Entwicklung der "brainworker", - Auffinden vergleichbarer Positionen/Tätigkeitsfelder in ausgewählten Organisationen, - Charakterisierung der Arbeitssituation von "brainworkers" in ausgewählten Unternehmen, - Analyse des Bildungs- und Weiterbildungshintergrunds von "brainworkers" und - Ausarbeitung von Vorschlägen für Aktionen der Gemeinschaft, die darauf zielen, die Bedingungen für das Ausbreiten der "brainworkers" zu verbessern. (IAB2)
"Kopfarbeiter" (brainworker). Typologie, Bildungshintergrund und Arbeitssituation
Keywords: T 1 Forschungsrichtungen; T 3 Forschungsmethoden; L 4 Medien & Technologien; S 6.4.3.4 Publizisten, Dolmetscher, Bibliothekare; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; Forschung und Entwicklung; Führungskraft; Systementwicklung; Informationsberuf; Arbeitskräftebedarf; Tätigkeitsfelder; Berufsausbildung; Berufsverlauf; Berufsproblem; Quantitative Angaben